From Nasion to Sellion: repositioning landmarks for radioprotection-tailored 3D cephalometric analysis - Marco Serafin; Benedetta Baldini; Elisa Boccalari; Salvatore Bocchieri; Sergio Sambataro; Chiarella Sforza; Giuseppe Baselli; Gianluca Martino Tartaglia; Alberto Caprioglio (Taylor & Francis Group, 2024)
Purpose The present study aimed to three-dimensionally evaluate the correlation between cephalometric measurements utilizing Sellion in place of Nasion.Material and methods A pilot study using 25 CBCTs was carried out to determine the required sample size, reaching a minimum of 136 patients was required to validate the correlation between Nasion(N)- and Sellion(Se)-related measurements. Eight landmarks were manually annotated on full cranium CBCTs, resulting in six skeletal and six cutaneous/skeletal measurements. Therefore, data were statistically analysed after outliers' detection and intraclass correlation coefficient (ICC) calculation. Pearson correlation coefficient (r) was used to assess the correlation between Nasion and Sellion measurements. At the end, simple linear regression was performed. Values of p < 0.01 and r > 0.80 were considered statistically and clinically relevant, respectively.Results ICC revealed a substantial degree of consistency. A total of 214 CBCTs were included in the present study. Pearson test revealed highly significant correlations for all the tested variables; the highest coefficient was found between N^Me^Go vs Se^Me^Go (r = 0.989, p < 0.001) while the lowest among SNA vs SSeA (ρ = 0.814, p < 0.001). Finally, linear regression provided the new norm range values for the Sellion-based measurements.Conclusion Pearson's coefficients between Sellion- and Nasion-related measurements exhibited significantly high levels of correlation, suggesting the potential use of Sellion-based measurements for innovative cephalometric analyses. This method might comply with radiation protection principles in CBCT-based orthodontic cephalometry.